Gamification in Secondary Education: An Innovative Strategy to Promote Student Motivation - Avello-Martínez, Raidell (Emerging Trends in Education, 2024)
The objective of the work was to evaluate the effectiveness of the implementation of gamification with Minecraft as a pedagogical strategy in the context of the 'San Pedro de Shaglli' Educational Unit to improve student motivation. A quantitative approach was used, with a pretest-posttest experimental design with control group. The sample consisted of 25 first- and second-year high school students and eight teachers from the same institution. The questionnaire Motivational Evaluation of Instructional Materials and the Game Motivation Scale were applied. An interview was also conducted with the teachers to find out their opinion about the use of gamification and Minecraft in the classroom. The results showed that gamification with Minecraft had a positive and significant impact on some dimensions of motivation, such as confidence, satisfaction and general motivation. In addition, it was evidenced that teacher’s value positively the use of the game as a pedagogical tool, but that they require support and training to integrate it properly in the classroom. Gamification with Minecraft can be an effective strategy to improve the motivation of high school students, but it also faces some challenges that should be taken into account.
Keywords: Motivation; Gamification; Minecraft; Pedagogical strategies